Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia - Robins, C. Richard (Zootaxa, 2005)
Cottus kanawhae, a member of the Cottus carolinae complex, is described from the New River System of Virginia and West Virginia.